The Effect Of Servant Leadership, Employee Engagement, And Career Development Policy On Organizational Commitment At Mulya Indah Permai Cooperative (MIP) - Mila Maliatul Husna; Didik Subiyanto; Nala Tri Kusuma (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the influence of servant leadership, employee engagement, and career development policies on organizational commitment at the Mulya Indah Permai Cooperative (MIP). Organizational commitment is an important factor in maintaining employee loyalty and engagement to support organizational sustainability. This study uses a quantitative approach with a census method, where all 40 employees of the Mulya Indah Permai Cooperative were surveyed. Data collection was conducted through the distribution of a likert scale questionnaire, which was then analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. The results of the study indicate that servant leadership has a positive effect on organizational commitment, employee engagement has a positive and significant effect on employee organizational commitment. Simultaneously, servant leadership, employee engagement, and career development policies have a positive and significan effect on organizational commitmen at Cooperative Mulya Indah Permai. These findings indicate that the implementation of a service-oriented leadership style, increased employee engagement, and clear and fair career development policies can increase employee commitment to the organizational. This study is expected to be taken into consideration by cooperative management in formulating human resource policies to increase employee organizational commitment.